Microcontroller Based High Brightness LED Lighting Control for Hybrid Vehicles - Ahmad, Nur Adzirah (Universiti Teknologi PETRONAS, 2016)
Automobile manufactures have been rapidly switching to LED headlights because they perform better than conventional halogen headlamps in terms of luminous flux and energy efficiency. To ensure optimal luminous flux and long operating life, LED headlights require an effective driver that can operate over a wide range of input and output voltage and provide immunity to automotive electrical transients. The intent of this project is to come up with a small size and cost effective universal driver using digital power control of switch mode power supply. To develop a better enhanced model, different existing models will be studied. Finally, design considerations from the study will be analysed. A laboratory prototype will be designed and tested to verify the feasibility.